Pengaruh Kesiapan Perubahan Organisasional Terhadap Pembelajaran Organisasional - Muafi, (Bisnis dan Manajemen, 2011)
This study examines if organizational change readiness will affect the organizational learning and using data from the Indonesiaan state-owned company that has recently been merged with other stated owned companies. This study devises a multifaceted model based on three constructs of organizational change readiness, namely aggressive attitude toward change, passive attitude toward change and the readiness attitude in coordination with change, and tests their effects on organizational learning, including knowledge creation and expantion. Empirical results indicate that organizational change readiness have positive affect to organizational learning.